El Baile de Los 41: Sexuality in 1900’s Mexico - Heib, Lauren (The Toro Historical Review, 2023)
During the dictatorial reign of Porfirio Diaz, a ball was discovered following noise complaint. That night, 42 men, a number of them members of Mexico’s elite, were found dancing together. This event brought so much scandal to Mexico, that the number 41 is still associated with homosexuality. The attendees, location, and the political climate of Mexican society played a pivital role in the dance's infamy. The Dance of the 41 served as a public catalyst for a changing sexual climate in Mexico, and therefore had a lasting impact regarding sexuality and gender roles in the following centuries.